TINJAUAN YURIDIS HUKUM KORBAN KEKERASAN SEKSUAL BERBASIS NILAI KEADILAN - Tomi Saladin (Mahkamah : Jurnal Kajian Hukum Islam, 2020)
Indonesia is a constitutional state based on Pancasila and the 1945 Constitution, so that every citizen has the same rights in the field of law as part of human rights (HAM). Human rights (human rights) are related to individual rights and community rights. One of the focuses of thought in every country today is the violation of human rights against women related to gender-based violence. Indonesia is one of the countries that has ratified the international convention on the elimination of violence against women. Violence is an attitude or action that is considered very disgraceful, so that the enforcement of ethical or moral norms in general comes from the awareness of everyone, so that a systemic approach is needed to prevent, overcome, and eliminate violence through the means of criminal law.